2021
DOI: 10.3892/or.2021.7934
|View full text |Cite
|
Sign up to set email alerts
|

JMJD2C triggers the growth of multiple myeloma cells via activation of β‑catenin

Abstract: Emerging evidence has indicated that histone modification and its related regulators are involved in the progression of multiple myeloma (MM) cells. In the present study, the expression of Jumonji C domain-containing 2 (JMJD2) was examined in both MM tissues and healthy controls. The roles of JMJD2C in the progression of MM were further investigated. The results revealed that the expression of JMJD2C, but not that of JMJD2A or JMJD2B, was increased in MM tissues compared with the healthy controls. The overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Results showed that KDM4C was elevated in the plasma of multiple myeloma patients and multiple myeloma cells. These results was consistent with the previous study 9) . Lv et al, revealed that KDM4C was elevated in bone marrow samples of multiple myeloma patients 9) .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Results showed that KDM4C was elevated in the plasma of multiple myeloma patients and multiple myeloma cells. These results was consistent with the previous study 9) . Lv et al, revealed that KDM4C was elevated in bone marrow samples of multiple myeloma patients 9) .…”
Section: Discussionsupporting
confidence: 94%
“…These results was consistent with the previous study 9) . Lv et al, revealed that KDM4C was elevated in bone marrow samples of multiple myeloma patients 9) . The high expression of KDM4C is also found in other cancers such as prostate cancer, ovarian cancer, colon cancer, non-small cell lung cancer (NSCLC), and glioblastoma 6-8, 19, 20) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There is a study which demonstrates how GSK-3 potentially has tumor-suppressive functions in MM; however, its activity is restrained by Akt activation, thereby resulting in the stabilization of Mcl-1 levels [ 157 ]. Another restrainer of GSK-3 in MM cells is the histone demethylase KDM4C, which is upregulated in MM patients and, when overexpressed in MM cell lines, increases β-catenin levels and activity while decreasing both the RNA and protein expression of GSK-3β [ 158 ]. Finally, there is evidence that lenalidomide (a drug widely used for treating MM patients [ 159 ]) induces activation of Wnt/β-catenin signaling.…”
Section: Gsk-3 Signaling In MMmentioning
confidence: 99%
“…KDM4B promotes carcinogenesis in estrogen receptor-positive breast cancer ( Yang et al, 2010 ; Kawazu et al, 2011 ) and has also been associated with poor outcomes in gastric cancer ( Wu et al, 2019 ), castration-resistant prostate cancer ( Sha et al, 2020 ) and osteosarcoma ( Liu et al, 2020 ). KDM4C promotes malignancy in multiple neoplasms, such as multiple myeloma ( Lv and Liu, 2021 ), glioblastoma ( Lee et al, 2021 ), and squamous cell carcinoma ( Labbé et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%